Nomogram of Nasal Bone Length in Euploid Fetus at 18-22 Weeks of Gestation in Bangladeshi Population (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Down syndrome (DS) is the most common chromosomal aneuploidy to result in a live birth. Prenatal diagnosis of the affected fetuses can be performed using variety of sonographic features. Within the 11 to 14 weeks gestational age (GA) window, increased nuchal translucency has been the hallmark for identifying fetuses with Down syndrome.Objective: To estimate the Nasal Bone Length (NBL) of fetuses at 18 to 22 weeks GA in Bangladeshi population and establish the Nomogram of it and finally compare it with that of Caucasian population.Materials and Methods: The prospective observational study was conducted in Aklima General Hospital Limited, Mirpur, Dhaka, Bangladesh in the Feto-maternal Medicine Unit under Obstetrics and Gynaecology Department for tenure from February 2014 to June 2019. After considering the inclusion and exclusion criteria, 500 antenatal subjects married to Bangladeshi partners with singleton pregnancies attending the routine antenatal outpatient department for an anomaly scan (18-22 weeks) were included and followed up in the study. The nasal bone length was measured from the base of the nose closest to the frontal bones to the farthest extent of ossification on the nose.Results: The nasal bone lengths of the fetuses at 18 to 22 weeks were measured in 500 cases where for 19 cases of 18 weeks of GA fetuses have a mean NBL of 4.6 mm, 75 cases of 19 weeks of GA fetuses have a mean NBL of 4.8 mm, 161 cases of 20 weeks of GA fetuses have a mean NBL of 5.1 mm, 169 cases of 22 weeks of GA fetuses have mean NBL of 5.8 mm and 76 cases of 22 weeks of GA fetuses have mean NBL of 6.2 mm which is significantly shorter than those of Caucasian population.Conclusion: The nasal bone lengths of the fetuses at 18 to 22 weeks were significantly shorter to those of the Caucasian population.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 48-50